2020
DOI: 10.1017/s0007114520001981
|View full text |Cite
|
Sign up to set email alerts
|

Higher ultra-processed food intake is associated with higher DNA damage in healthy adolescents

Abstract: Ultra-processed food is one of the main contributors to energy supply and consumption in food systems worldwide, and evidence of their detrimental health outcomes in humans is emerging. This study aimed to assess ultra-processed food intake and its association with urinary levels of 8-hydroxy-2'-deoxyguanosine (8-OHdG), a biomarker of DNA oxidative damage, in 139 healthy adolescents in Karaj city in Iran. Usual dietary intake was measured using a 168-item validated food frequency questionnaire. The daily intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 97 publications
0
16
0
2
Order By: Relevance
“…Preclinical animal and cell models also report the implication of sodium nitrate (used as a preservative to increase shelf life) and titanium dioxide (used as white food pigment) in carcinogenesis 115,116 . Relatedly, a recent observational study in adolescents reported that higher versus lower consumption of ultraprocessed food was associated with higher DNA oxidative damage as measured by urinary concentrations of 8‐hydroxy‐2′‐deoxyguanosine 117 . Indeed, the initiation and development of cancer have been associated with oxidative stress via DNA mutation and damage 118 .…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical animal and cell models also report the implication of sodium nitrate (used as a preservative to increase shelf life) and titanium dioxide (used as white food pigment) in carcinogenesis 115,116 . Relatedly, a recent observational study in adolescents reported that higher versus lower consumption of ultraprocessed food was associated with higher DNA oxidative damage as measured by urinary concentrations of 8‐hydroxy‐2′‐deoxyguanosine 117 . Indeed, the initiation and development of cancer have been associated with oxidative stress via DNA mutation and damage 118 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a study on 139 adolescents in Iran showed a significant urinary biomarker of DNA oxidative damage associated with higher intake of UPF (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Landecker reviewed and argued that some genomes immersed in food molecules might be more susceptible to epigenetic lability than others predisposing them to a determined susceptibility to disease ( 108 ). On the one hand, some bioactive food compounds are able to exert protective properties, and in contrast, recently, it has been studied that some components from western-type diets, ultraprocessed food, and their lack of essential nutrients also modulates negatively epigenetics machinery ( 109 , 110 ).…”
Section: Nutrition Epigenetics and Mdd: Is There A Link?mentioning
confidence: 99%